The Impact of Currency Depreciation on Egyptian Exports: A firm-level study - ElGhorab, Noor (AUC Knowledge Fountain, 2025)
This study investigates the impact of real exchange rate depreciations of the Egyptian Pound on the intensive and extensive margins of firm-level exports in the years 2008, 2013, 2016, and 2020 using a comprehensive dataset of over 7,000 firms from the World Bank Enterprise Survey. Employing a firm-level fixed effects model, the study finds that real depreciation boosts export performance by 5.7 percentage points and 6.2 percentage points at the intensive and extensive margins respectively. Results also indicate a positive relationship between firm exports and firm size, foreign ownership, and firms with greater reliance on imports in their inputs. Additionally, firms with higher import intensity were able to leverage competitiveness gains more strongly than they were hurt by higher input costs following a depreciation. These findings highlight the importance of complementary policies—such as mitigating input-cost shocks, facilitating global market integration, and assessing Egypt’s sectoral competitiveness to fully leverage exchange rate adjustments for export promotion in Egypt.